2017
DOI: 10.1016/j.jbior.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase II (CK2), Glycogen Synthase Kinase-3 (GSK-3) and Ikaros mediated regulation of leukemia

Abstract: Signaling networks that regulate cellular proliferation often involve complex interactions between several signaling pathways. In this manuscript we review the crosstalk between the Casein Kinase II (CK2) and Glycogen Synthase Kinase-3 (GSK-3) pathways that plays a critical role in the regulation of cellular proliferation in leukemia. Both CK2 and GSK-3 are potential targets for anti-leukemia treatment. Previously published data suggest that CK2 and GSK-3 act synergistically to promote the phosphatidylinositol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 137 publications
(177 reference statements)
0
17
0
Order By: Relevance
“…Another potential target is the serine/threonine protein kinase CK2, which is a posttranslational activator of constitutive PI3K/Akt signaling in T-ALL cells by inhibiting PTEN (Silva et al, 2008). CK2 was shown to play a key role in promoting the proliferation of ALL cells of both B and T cell origin (Gomes et al, 2014; Gowda et al, 2017a, 2017b; Silva et al, 2008) and was recently shown to be required for optimal IL-7-mediated signaling, and consequent IL-7-dependent T-ALL cell cycle progression and viability (Melao et al, 2016). CK2 was also required for the viability of mutant IL-7R-expressing leukemia T-cells.…”
Section: A Promise… Targeting Il-7r-mediated Signaling In T-all For Tmentioning
confidence: 99%
“…Another potential target is the serine/threonine protein kinase CK2, which is a posttranslational activator of constitutive PI3K/Akt signaling in T-ALL cells by inhibiting PTEN (Silva et al, 2008). CK2 was shown to play a key role in promoting the proliferation of ALL cells of both B and T cell origin (Gomes et al, 2014; Gowda et al, 2017a, 2017b; Silva et al, 2008) and was recently shown to be required for optimal IL-7-mediated signaling, and consequent IL-7-dependent T-ALL cell cycle progression and viability (Melao et al, 2016). CK2 was also required for the viability of mutant IL-7R-expressing leukemia T-cells.…”
Section: A Promise… Targeting Il-7r-mediated Signaling In T-all For Tmentioning
confidence: 99%
“…Casein kinases have previously been shown to regulate PI3K signaling by phosphorylation of PTEN (37). This activation of PI3K signaling by CSNK2A1 is synergistic with GSK-3, which does not phosphorylate BCAP in our in vitro kinase assay (38). Casein kinases have also been linked to innate immunity, by phosphorylation of various proteins in the NF-B pathway (30,39,40).…”
Section: Bcap Phosphorylation and Inflammatory Signallingmentioning
confidence: 62%
“…Casein kinases have previously been shown to regulate PI3K signaling by phosphorylation of PTEN (37). This activation of PI3K signaling by CSNK2A1 is synergistic with GSK-3, which does not phosphorylate BCAP in our in vitro kinase assay (38). Casein kinases have also been linked to innate immunity, by phosphorylation of various proteins in the NF-κB pathway (30, 39, 40).…”
Section: Discussionmentioning
confidence: 83%